Literasi Terhadap Teknologi Mata Uang Digital (Cryptocurrency) Pada Pendengar Setia Radio Prokom FEBI IAIN Pontianak - Julianto Julianto (Lembaga Pengembangan Kinerja Dosen, 2023)
Bitcoin and Altcoin are digital currencies (cryptocurrencies) that use blockchain technology, a technology that can monitor, supervise, record, and record every transaction that occurs in digital currency. Bitcoin is decentralized, meaning it is spread everywhere, not centralized and cannot be regulated by authorities or other institutions. In making transactions, it is very necessary to recognize digital currencies such as identity, core business, projects being developed, volume of demand and supply, and other indicators. The need to find out information about coins/crypto tokens before trading, is a very helpful thing for traders because of concerns about coins/tokens that are indicated as scam or rugpull. Coinmarketcap.com and coingecko are data provider sites related to bitcoin and altcoins around the world, which can help find and analyze related information about tokens/cryptocoins to be traded, but do not guarantee accuracy, but can minimize the occurrence of greater losses. Digital currencies provide business opportunities and loopholes to be able to generate profit from every coin/token traded, but on the other hand these assets are risky for traders and investors due to their high volatility which makes market price movements difficult to predict (unpredictable). To be able to overcome this problem it is necessary to manage finances by taking 10% for trading from the main salary earned, dividing which assets are needed for trading and which are for daily / other living needs and self-control well, when is it time to trade, rest, and when to pause. That way it can save other assets when the other asset is experiencing a decline, so it doesn't disturb the main asset.